2017
DOI: 10.1371/journal.pmed.1002272
|View full text |Cite
|
Sign up to set email alerts
|

Fine-mapping of the human leukocyte antigen locus as a risk factor for Alzheimer disease: A case–control study

Abstract: BackgroundAlzheimer disease (AD) is a progressive disorder that affects cognitive function. There is increasing support for the role of neuroinflammation and aberrant immune regulation in the pathophysiology of AD. The immunoregulatory human leukocyte antigen (HLA) complex has been linked to susceptibility for a number of neurodegenerative diseases, including AD; however, studies to date have failed to consistently identify a risk HLA haplotype for AD. Contributing to this difficulty are the complex genetic or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 78 publications
0
65
0
Order By: Relevance
“…These results suggest that mechanistically, PHS may, in part, be capturing influence from other AD pathological pathways beyond amyloid and tau, a reflection of the complexity underlying AD pathogenesis involving neuroinflammation and immune regulation [3, 26], neurovascular [30], mitogenic and oxidative stress signaling pathways [29]. Alternatively, our findings may reflect that risk factors for pathology are not equivalent to pathology.…”
Section: Discussionmentioning
confidence: 89%
“…These results suggest that mechanistically, PHS may, in part, be capturing influence from other AD pathological pathways beyond amyloid and tau, a reflection of the complexity underlying AD pathogenesis involving neuroinflammation and immune regulation [3, 26], neurovascular [30], mitogenic and oxidative stress signaling pathways [29]. Alternatively, our findings may reflect that risk factors for pathology are not equivalent to pathology.…”
Section: Discussionmentioning
confidence: 89%
“…The molecules encoded by the major histocompatibility complex (MHC) regions regulate the innate and adaptive arms of human immune response through antigen presentation, inflammation regulation and the complement system and the impact of this region in various immune-mediated conditions, including neurological diseases, has long been recognized. [4][5][6][7][8][9] The human MHC gene family maps to chromosome 6. With a size of nearly 5 Mbp it encodes approximately 165 protein-coding genes, many of them immune-related, 10 and comprises approximately 0Á13% of the human genome.…”
Section: The Human Major Histocompatibility Complex Region and Neurolmentioning
confidence: 99%
“…Finally, an HLA imputation-based analysis of 5919 European-ancestry AD Caucasian patients and 5771 controls identified the extended haplotype A*03:01~B*07:02~DRB1*15:01~DQA1*01:02~DQB1*06:02 as being associated with AD risk (P = 9Á6 9 10 À4 , OR = 1Á21) 8 in individuals who are negative for APOE 4. 8 The authors also found an association of the class I haplotype A*03:01~B*07:02, with higher CSF amyloid levels and a dose-dependent association of the DR15 haplotype with greater rates of cognitive decline and baseline levels of chemokine CC-4.…”
Section: Hla and Parkinson's Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…In other studies, however, these same alleles/combinations thereof have been established in neurological disorders such as Alzheimer's disease and multiple sclerosis, Parkinson's disease, narcolepsy, and autism (Table 4). [85][86][87] In addition, an increased risk of several inflammatory diseases such as sarcoidosis, especially nonresolving, pediatric-onset inflammatory bowel diseases (both Crohn's disease and ulcerative colitis), adult ulcerative colitis, and systemic lupus erythematosus in European descent, African-American, and Hispanic populations have been associated with DRB1*15:01/15:03 -related haplotypes. 35,38,88,89 Schizophrenia is another chronic neurologic disorder that affects nearly 1% of the world's population.…”
Section: Hla and Disease Associationsmentioning
confidence: 99%